-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathPraeclarum_theorema.lean
66 lines (53 loc) · 1.38 KB
/
Praeclarum_theorema.lean
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
-- Praeclarum_theorema.lean
-- Praeclarum theorema
-- José A. Alonso Jiménez <https://jaalonso.github.io>
-- Seville, January 21, 2025
-- ---------------------------------------------------------------------
-- ---------------------------------------------------------------------
-- Prove the [praeclarum theorema](https://tinyurl.com/25yt3ef9) of
-- Leibniz:
-- (p → q) ∧ (r → s) → ((p ∧ r) → (q ∧ s))
-- ---------------------------------------------------------------------
import Mathlib.Tactic
variable (p q r s : Prop)
-- Proof 1
-- =======
example:
(p → q) ∧ (r → s) → ((p ∧ r) → (q ∧ s)) :=
by
intro ⟨hpq, hrs⟩ ⟨hp, hr⟩
-- hpq : p → q
-- hrs : r → s
-- hp : p
-- hr : r
constructor
. -- q
exact hpq hp
. -- s
exact hrs hr
-- Proof 2
-- =======
example:
(p → q) ∧ (r → s) → ((p ∧ r) → (q ∧ s)) :=
by
intro ⟨hpq, hrs⟩ ⟨hp, hr⟩
-- hpq : p → q
-- hrs : r → s
-- hp : p
-- hr : r
exact ⟨hpq hp, hrs hr⟩
-- Proof 3
-- =======
example:
(p → q) ∧ (r → s) → ((p ∧ r) → (q ∧ s)) :=
fun ⟨hpq, hrs⟩ ⟨hp, hr⟩ ↦ ⟨hpq hp, hrs hr⟩
-- Proof 4
-- =======
example:
(p → q) ∧ (r → s) → ((p ∧ r) → (q ∧ s)) :=
fun ⟨hpq, hrs⟩ hpr ↦ And.imp hpq hrs hpr
-- Proof 5
-- =======
example:
(p → q) ∧ (r → s) → ((p ∧ r) → (q ∧ s)) :=
by aesop